2014
DOI: 10.1093/infdis/jiu165
|View full text |Cite
|
Sign up to set email alerts
|

Protection Versus Pathology in Aviremic and High Viral Load HIV-2 Infection—The Pivotal Role of Immune Activation and T-cell Kinetics

Abstract: Background. Many human immunodeficiency virus (HIV)–2-infected individuals remain aviremic and behave as long-term non-progressors but some progress to AIDS. We hypothesized that immune activation and T-cell turnover would be critical determinants of non-progressor/progressor status.Methods. We studied 37 subjects in The Gambia, West Africa: 10 HIV-negative controls, 10 HIV-2-infected subjects with low viral loads (HIV-2-LV), 7 HIV-2-infected subjects with high viral loads (HIV-2-HV), and 10 with HIV-1 infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
1
14
1
Order By: Relevance
“…We and others previously reported that thymic function is preserved in HIV-2-infected individuals with low viral load (25). It was also recently shown that HIV-2 infection in thymocytes is impaired (26,27), which may contribute to the maintenance of high CD4 + T cell counts in HIV-2-infected patients. In this study, we measured sjTREC levels in total PBMC to estimate thymic function in HIC2.…”
Section: Cd45ramentioning
confidence: 74%
“…We and others previously reported that thymic function is preserved in HIV-2-infected individuals with low viral load (25). It was also recently shown that HIV-2 infection in thymocytes is impaired (26,27), which may contribute to the maintenance of high CD4 + T cell counts in HIV-2-infected patients. In this study, we measured sjTREC levels in total PBMC to estimate thymic function in HIC2.…”
Section: Cd45ramentioning
confidence: 74%
“…However, HIV-2 infection represents a natural model of retroviral disease in which nonprogression and lower levels of immune activation appear to be the norm [73]. Importantly, viral replication and high viremia are not sufficient to explain the immunopathogenesis of all retroviruses because high-level viremia without immune cell activation may be tolerated without disease, as in the case of sooty mangabey SIV infection [73,74].…”
Section: Samhd1: Friend or Foe?mentioning
confidence: 99%
“…However, HIV-2 infection represents a natural model of retroviral disease in which nonprogression and lower levels of immune activation appear to be the norm [73]. Importantly, viral replication and high viremia are not sufficient to explain the immunopathogenesis of all retroviruses because high-level viremia without immune cell activation may be tolerated without disease, as in the case of sooty mangabey SIV infection [73,74]. These differences have led to the hypothesis that the immune system is able to differentially recognize and trigger an innate immune response through sensing of viral elements (for a recent review, see [75]), leading to aberrant cell activation and immunopathogenesis.…”
Section: Samhd1: Friend or Foe?mentioning
confidence: 99%
“…The introduction of stable isotope labeling into the field of immunology has paved the way for reliable quantification of T-cell dynamics. Previous studies based on 2 Hglucose or 2 H 2 O labeling demonstrated the great potential of this technique for studying lymphocyte turnover [7,9,11,12,16,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%